PENERAPAN MESIN PENGERING JAGUNG UNTUK PETANI TEBUWUNG - Marleno, Risma; Triadmojo, Hasbi; Alif Isto K, Muchammad (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
Extend the shelf life of food products so that they can be consumed longer. Corn is an important food commodity in Tebuwung Village, Dukun District, Gresik Regency because it is a food other than rice. To extend the shelf life of corn, it is necessary to go through a drying process. One of the drying equipment that can be used is rotary rotating type dryer (rotary dryer). The heat source of the dryer can come from corn stalks to reduce the scent as a source of burning heat. The problem is there is no available drying equipment suitable for corn drying in Tebuwung Village, Dukun District, Gresik Regency. For this reason, a study was conducted to design a rotary type drying machine for heat-sourced corn originating from the burning of corn cobs. This study aims to produce a rotary type corn drying machine with a source of burning corn cobs. The test parameter is the rotating drying cylinder which affects the drying time of corn in the drying chamber. Through this research, a rotary type drying machine has been produced for drying corn in Tebuwung Village, Dukun District, Gresik Regency. The test results with a rotating cylinder speed ratio of 1400 rpm and 280 rpm are 42 minutes long drying and require power of 522.85 watts with electricity costs of Rp. 500.24 for 900 VA and Rp. 542,936 for 1,300 VA power